Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Mazor, Tessa; Pitcher, C. Roland; Rochester, Wayne; Kaiser, Michel J.; Hiddink, Jan G.; Jennings, Simon; Amoroso, Ricardo; McConnaughey, Robert A.; Rijnsdorp, Adriaan D.; Parma, Ana M.; Suuronen, Petri; Collie, Jeremy; et al. (Fish and fisheries (Oxford, England), 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.